2018
DOI: 10.5551/jat.rv17023
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Diabetic Dyslipidemia

Abstract: Accumulating clinical evidence has suggested serum triglyceride (TG) is a leading predictor of atherosclerotic cardiovascular disease, comparable to low-density lipoprotein (LDL)-cholesterol (C) in populations with type 2 diabetes, which exceeds the predictive power of hemoglobinA1c. Atherogenic dyslipidemia in diabetes consists of elevated serum concentrations of TG-rich lipoproteins (TRLs), a high prevalence of small dense low-density lipoprotein (LDL), and low concentrations of cholesterol-rich high-density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
273
2
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(306 citation statements)
references
References 103 publications
13
273
2
18
Order By: Relevance
“…Serum lipids are known to be significantly impacted by insulin 24 . Hypertriglyceridemia is a common serum lipid abnormality associated with diabetes, due either to insulin resistance or deficiency.…”
Section: Metabolic Changesmentioning
confidence: 99%
“…Serum lipids are known to be significantly impacted by insulin 24 . Hypertriglyceridemia is a common serum lipid abnormality associated with diabetes, due either to insulin resistance or deficiency.…”
Section: Metabolic Changesmentioning
confidence: 99%
“…Dyslipidemia Most (60-90%) T2D patients are dyslipidemic [6][7][8]. T2D dyslipidemia triad (hypertriglyceridemia, increase in sdLDL-C, decrease in HDL-C) is driven by increase in VLDL-triglycerides (VLDL-TG) [141]. Increase in VLDL-TG is driven by hyperactive mTORC1 due to promoting hepatic steatosis, phosphatidylcholine synthesis [142], and disruption of the IR-Akt-FOXO1 pathway.…”
Section: Non-glycemic Context Of T2d Response To Insulinmentioning
confidence: 99%
“…FoxO1 activation results in transcriptional activation of the microsomal TG transfer protein (MTP) [143] and apoCIII [144]. MTP combines the VLDL ingredients to form the lipoprotein particle, and apoCIII suppresses plasma VLDL-TG lipolysis by lipoprotein lipase [141]. Of note, T2D dyslipidemia is avoided upon knocking out the IR [59], implying an obligatory role for insulin in promoting T2D dyslipidemia [60].…”
Section: Non-glycemic Context Of T2d Response To Insulinmentioning
confidence: 99%
“…It has also been shown that the incidence of CAD differs by patterns of lipoprotein subclass [11]. For example, the atherogenic lipoprotein, small dense LDL-C (sdLDL-C), is often observed in patients with T2DM or insulin resistance [12]. Although the effects of antidiabetic agents on the patterns of lipoprotein subclass are assumed to be pivotal, an evaluation testing this assumption has not yet been performed in patients treated with DPP-4 inhibitors, which are among the most frequently prescribed antidiabetic agents [13,14].…”
Section: Introductionmentioning
confidence: 99%